Synthesis of 1,2-divinylcyclopropanes by metal-catalyzed cyclopropanation of 1,3-dienes with cyclopropenes as vinyl carbene precursors - González, Jesús; de la Fuente, Alba; González, María J.; Díez de Tejada, Laura; López, Luis A.; Vicente, Rubén (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of 1,2-divinylcyclopropanes by the reaction of cyclopropenes with 1,3-dienes is reported. The process relies on the ability of ZnCl2 or [Rh2(OAc)4] to generate metal–vinyl carbene intermediates from cyclopropenes, which effect cyclopropanation of 1,3-dienes. Most of the reactions proceeded in reasonable yields while the diastereoselectivity strongly depends on the structure of the diene. An example of an intramolecular process as well as the use of furan and 1,4-cyclohexadiene as dienes are also reported.
Keywords: cyclopropanation; cyclopropenes; dienes; divinylcyclopropanes; transition metal catalysis